'There are no more secrets': acceptability of a family-centered model of care for HIV positive children in Eswatini - Philisiwe N. Khumalo; Leila Katirayi; Kim Ashburn; Caspian Chouraya; Lydia Mpango; Nobuhle Mthethwa; Lynne M. Mofenson (BMC, 2020)
Abstract Background HIV-positive children have lagged adults on retention in HIV care and viral suppression. To address this gap, Eswatini's Ministry of Health started a pilot family-centered HIV care model (FCCM) targeting HIV-positive children under 20 years old and their families. Methods We conducted semi-structured in-depth interviews with 25 caregivers and 17 healthcare workers (HCWs) to assess acceptability of FCCM in four pilot FCCM health facilities in Hhohho region of Eswatini. Thematic analysis with inductive and deductive codes was used to identify salient themes. Results Caregivers and HCWs reported FCCM benefits including strengthening the family bond, encouragement for family members to disclose their HIV status and supporting each other in taking antiretroviral drugs. Caregivers reported that they spent fewer days in clinic, experienced shorter waiting times, and received better counseling services in FCCM compared to the standard-of-care services. FCCM implementation challenges included difficulty for families to attend clinic visits together (e.g., due to scheduling conflicts with weekend Teen Support Club meetings and weekday FCCM appointments). Both HCWs and caregivers mentioned difficulty in sharing sensitive health information in the presence of other family members. HCWs also had challenges with supporting caregivers to disclose HIV status to children and managing the larger group during clinic visits. Conclusions FCCM for HIV-positive children was acceptable to both caregivers and HCWs, and they supported scaling-up FCCM implementation nationally. However, special considerations should be made to address the challenges experienced by participants in attending clinic visits together as a family in order to achieve the full benefits of FCCM for HIV positive children.